Techno-Economic Analysis of NiFe2O4 Nanoparticle Industry Using Sonochemical Synthesis Method - Rachel Gabriella; Muhammad Aldin Nur Zen; Fatih Izzul Haq; Silmi Ridwan Putri; Asep Bayu Dani Nandiyanto (Universitas Komputer Indonesia, 2021)
The purpose of this paper is to carry out an economic and industrial evaluation on an industrial scale of NiFe2O4 production using sonochemical synthesis methods. The method used is to calculate gross profit margin (GPM), payback period (PBP), cumulative net present value (CNPV), total investment cost (TIC) and profitability index (PI). NiFe2O4 nanoparticles were synthesized with the main raw materials being Fe(NO3)3.9H2O, Ni(NO3)2.6H2O, and NaOH (1:2:8). The calculation results of GPM and CNPV/TIC from the NiFe2O4 industry using the sonochemical synthesis method show the payback period (PBP) in the third year. So that in the third year onwards it can be predicted that the industry will experience profits. This research is expected to be a reference for technical and economic analysis to produce NiFe2O4 in humidity sensor applications on an industrial scale.